Im just confused as to how this step (1) [ -ln l 150 - y l = (t / 200) - ln 130 ], simplified into this (2) l 150 - y l = 130e^(-t/200) The only part i dont understand about this is how (t/200) in (1) became (-t/200) in (2) Thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by johntuan Im just confused as to how this step (1) [ -ln l 150 - y l = (t / 200) - ln 130 ], simplified into this (2) l 150 - y l = 130e^(-t/200) The only part i dont understand about this is how (t/200) in (1) became (-t/200) in (2) Thanks Note that $\displaystyle -\ln\left|150-y\right|=\frac{t}{200}-\ln 130\implies \ln\left|150-y\right|=-\frac{t}{200}+\ln 130$ So $\displaystyle \left|150-y\right|=e^{-\frac{t}{200}+\ln 130}=e^{-\frac{t}{200}}e^{\ln 130}=130e^{-\frac{t}{200}}$ Does this make sense?
View Tag Cloud